BREAKING THE BUBBLE—ADDRESSING MANAGERS’ CULTURAL BIASES IN DESIGNING TOURIST EXPERIENCES - Aleksandra S. Dragin; Uglješa Stankov; Maja Mijatov Ladičorbić; Miroslav D. Vujičić; James Kennell; Alberto Calahorro-López (Zbornik Radova: Geografski institut "Jovan Cvijić", 2024)
Although cross-cultural interactions and cultural bubbles have been researched extensively in tourism, these issues have often been viewed one-sidedly. More precisely, in contemporary literature, cultural bubbles are mostly considered one-sided biases that prevent tourists from fully enjoying the culture of their hosts. Besides that, it is important to bear in mind that a tourist offer itself is also formed from the perspectives of tourism experience designers and tourism managers. Therefore, it is important to consider how the perception of a tourist offer is distorted by looking from inside the bubble of tourist culture. This paper highlights managers’ cultural biases in designing tourist experiences, which have often been overlooked in cross-cultural tourism studies. It is crucial to have this discussion now so that the global tourist industry can continue to provide local experiences, as tourism managers and employees in the sector are increasingly interacting with people from diverse cultural contexts. This might be beneficial for the cultural expression of destinations, on the one hand, as well as for providing more valuable experiences for tourists, on the other.